A system for the automated finding of inefficiencies and errors in parallel programs - Andreev, D.Yu.; Antonov, A.S.; Voevodin, Vad.V.; Zhumatii, S.A.; Nikitenko, D.A.; Stefanov, K.S.; Shvets, P.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2013)
The first version of a system for the automated finding of inefficiencies and errors in parallel programs is considered. The developed algorithms devoted for the automated finding of logic and semantic errors in MPI parallel programs are implemented in this system. The system realizes the search for templates of inefficient behavior of parallel programs written on the UPC language. The user interaction is performed via a specialized web portal that provides the access to available high performance computing resources. This work was supported by the Ministry of Education and Science of Russian Federation (contract 14.514.11.4062). The paper is recommended for publication by the Program Committee of the International Scientific Conference «Scientific Services and Internet: all bounds of parallelism» ((http://agora.guru.ru/abrau2013)).